2008
DOI: 10.1186/1471-2431-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-admission hypothermia among high-risk Nigerian newborns

Abstract: Background: Facilities which manage high-risk babies should frequently assess the burden of hypothermia and strive to reduce the incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 12 publications
13
49
3
Order By: Relevance
“…According to our study result, fi fty seven percent neonates had low birth weight and of them 40% had hypothermia at admission. This study result is consistent with earlier reports 2,5,16,18 . The association of prematurity (<37 weeks) and hypothermia was not unexpected, because the physical characteristics of premature infants predispose to a mismatch between heat production and heat exchange with the ambient environment.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…According to our study result, fi fty seven percent neonates had low birth weight and of them 40% had hypothermia at admission. This study result is consistent with earlier reports 2,5,16,18 . The association of prematurity (<37 weeks) and hypothermia was not unexpected, because the physical characteristics of premature infants predispose to a mismatch between heat production and heat exchange with the ambient environment.…”
Section: Discussionsupporting
confidence: 96%
“…Reports from different Asian and African developing countries show that neonatal hypothermia is common and has been regarded as a major contributor cause of signifi cant morbidity 1,2,3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the conditions in similar Nigerian tertiary hospitals [10,12]. However, no Nigerian research publication has been able to synthesize any solutions for the reduction of the mortalities [13]; hence prompting the introduction of the new techniques that led to the present investigation.…”
Section: Discussionsupporting
confidence: 72%
“…A number of hospital-based studies in such settings have demonstrated that thermal stress is common 9, 10 , and more than one-half of newborns experience hypothermic episodes 1, 2, 10–12 . Some hospital-based studies have observed higher mortality risk among admitted babies with hypothermia broadly defined as any measure <36.0°C 3 or 36.5° 3, 13, 14 . While these studies indicate that hypothermia may be an important contributor to neonatal mortality, they are limited by lack of adjustment for age of infants at measurement and are predominately focused on sick infants presenting to tertiary care units.…”
Section: Introductionmentioning
confidence: 99%